Clinical Profile of Diabetic Papillopathy Patients at a Tertiary Care Hospital in Indonesia - Abdullah, Rizqy; Agustini, Lukisiari; Sunreza Millenia, Maasa; Susanto, Hermawan (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2023)
Background: Diabetic Papillopathy (DP) is a rare complication of Diabetes mellitus (DM) which affects visual function. The purpose of this study was to describe the profile of DP patients at a tertiary care hospital in Surabaya, Indonesia. Methods: A descriptive retrospective study using electronic medical records of DP patients at the eye outpatient unit of Dr. Soetomo General Hospital in Surabaya between 2017 and 2020. Demographic data such as clinical characteristics, and history of DM were included. Levels of fasting blood glucose (FBG), 2-hour post-prandial blood sugar (PPG), and HbA1c were taken. Examination of the optic disc and retina determines the diagnosis of DP. Results: There were 27 cases of DP with the mean age of the patients being 49.3±9.3 years, predominance in the 46-55 years group (59.26%). Patients with DP had average systolic and diastolic blood pressure was 131.74±21.94 mmHg, and 86.00±15.89 mmHg, and an average BMI of 24.6 ±3.54 kg/m2 (62.96%). Most patients had a history of type 2 DM (96.29%), mean fasting blood sugar (FBG) and postprandial blood (PPG) was 225±83.3 mg/dL, and 147.81±59.72 mg/dL; and HbA1c 8.6±1.5 mg%. Conclusion: DP findings are relatively low in DM patients, however, DP could result in decreased visual acuity and quality of life so a proper ocular examination is important in DM patients.